(untitled) (Altre Modernità, 2022)
The global spread of English has resulted in new varieties and cultures being associated with it; Cultural Linguistics studies these by emphasising the relationship between language and culturally-constructed conceptualisations. English is often seen as negative for local languages, especially in post-colonial contexts; however, speech communities can develop new varieties by localising it through ‘glocalisation’ or ‘nativisation’. The purpose of this paper is to investigate these notions by considering Singlish, the colloquial variety of Singapore English. Here, the adoption of English words has contributed to the creation of a localised variety, though this hybridisation is often seen as a corruption. The long-lasting debate around it has seen direct intervention of the Government and reactions of linguistic resistance or “chutzpah” coming from Singlish speakers, in an attempt to reclaim Singlish as the true expression of Singaporean identity. The analysis examines English words in two online Singlish dictionaries (A Dictionary of Singlish and Singapore English and The Coxford Singlish Dictionary), in order to understand the cultural conceptualisations they represent. A cross-checking with the Oxford English Dictionary further highlights differences with the standard: this helps demonstrate that English expressions can become the keywords of a culture of non-native speakers and contribute to a redefinition of its linguistic identity, rather than cancelling it.